Genetic stock structure and estimation of abundance of swordfish (Xiphias gladius) in South Africa - West, Wendy (Department of Biological Sciences, 2016)
Targeted fishing for swordfish (Xiphias gladius) in South Africa began in the mid-1980s by recreational anglers. The recreational fishery dwindled with the near-shore resources at the onset of experimental pelagic longlining from 1997. The commercial fishery was formalised in 2005 with the issuing of 10-year long term rights to swordfish- and tuna-directed vessels. South Africa's swordfish catches reached a peak in 2002 at 1 187 t, and have been on the decline with average catches of 372 t over the last 5 years. South Africa straddles two ocean basins, the Indian and Atlantic Ocean and currently the jurisdictions of the Indian Ocean Tuna Commission (IOTC) and International Commission for the Conservation of Atlantic Tuna (ICCAT) are separated by a management boundary at 20°E. Consequently, all tunas and billfish stocks with the exception of the southern bluefin tuna (Thunnus maccoyii), are artificially divided into Atlantic and Indian Ocean stocks along this boundary, regardless of their true stock structure and distribution. Since questions remain about the origin of South African caught swordfish, it remains uncertain if the artificial split in reporting stock indices indeed reflects a biological meaningful separation of stocks. Previous recent genetics studies have confirmed genetic differentiation between the Atlantic and Indian Ocean stocks though there is no agreement on the direction of gene flow and where, or indeed if, a genetically relevant boundary exists. Eleven microsatellite loci were included in this study of the fine scale population structure of swordfish caught relatively close inshore. Despite the poor quality of the DNA samples, muscle material of 267 swordfish caught in 2005 around the entire range of South Africa's coastline was utilised. A posterior predictive map of admixture proportions produced a potential admixture zone between 14°E and 27°E. There is evidence of gene flow and migration in this area in both directions, though the evidence for weak differentiation suggests that the Indian Ocean and Atlantic Ocean contain separate stocks and that swordfish stocks coexist around South Africa but return to their ocean of origin to reproduce. Due to passive drift of larvae and active dispersal of adults that have wide environmental parameter limits that extend across this area, swordfish would be prone to admixture and genetic homogenisation.